Single-ion composite solid electrolytes and their preparation and application, lithium-ion batteries
By using ethylene carbonate and sulfonic acid compounds containing amide groups in lithium-ion batteries for polymerization and lithiation, the problems of poor ion conductivity and lithium ion migration of solid electrolytes in lithium-ion batteries are solved, and a high-performance and low-cost lithium-ion battery electrolyte membrane is achieved.
Patent Information
- Application Number
- CN202311701206.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-12-12
AI Technical Summary
The solid electrolytes of existing lithium-ion batteries do not perform well in terms of ion conductivity and lithium ion migration number, and the mechanical properties of conventional polymer solid electrolytes are not sufficient to prevent the growth of lithium dendrites.
By polymerizing ethylene carbonate with an amide group-containing sulfonic acid compound under the action of an initiator, a solid polymer electrolyte with a larger molecular weight is formed, and its ionic conductivity is improved by lithiation treatment.
Solid-state electrolytes with high ion conductivity and lithium ion migration number have been achieved, which significantly improves the performance of lithium-ion batteries and reduces production costs, making them suitable for industrial applications.
Smart Images

Figure CN117691178B_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a single ion composite solid electrolyte and preparation and application thereof, and a lithium ion battery. Background technology:
[0002] Due to the advantages of high energy density, high power density, and long life, lithium-ion batteries are currently widely used in power vehicles and energy storage fields. Traditional lithium-ion batteries mainly use organic electrolytes, which have the disadvantages of easy leakage, volatility, and flammability. When impacted by external forces, the electrolyte will leak or even explode. In addition, liquid electrolytes cannot prevent the growth of lithium dendrites. Lithium dendrites gradually grow and pass through the diaphragm, causing a short circuit between the positive and negative electrodes, thereby causing a series of safety problems. Solid electrolytes have higher energy density and better safety performance and have attracted much attention, becoming an important direction for lithium-ion battery research.
[0003] Solid electrolytes can be divided into oxide solid electrolytes, sulfide solid electrolytes, and polymer solid electrolytes according to their composition. The oxide solid electrolyte has a high ionic conductivity, but is very brittle. Its contact with the positive and negative electrodes is point contact, which leads to a large interface impedance, hindering the migration of lithium ions, and limiting its application scenarios. Sulfide solid electrolytes have the highest ionic conductivity, which has exceeded the level of liquid electrolytes, but they produce toxic hydrogen sulfide in the air, so the cost is high and the production conditions are harsh. Polymer solid electrolytes have good flexibility, can be in close contact with the positive and negative electrodes, are relatively stable in the environment, have good processability, and can be used to prepare large-size batteries, but their room temperature ionic conductivity is low, the electrochemical window is narrow, and the mechanical properties are poor, which limits their application prospects.
[0004] In addition, conventional polymer solid electrolytes have poor mechanical properties and it is difficult to prevent the growth of lithium dendrites by their own mechanical properties. As charging and discharging proceed, anions accumulate and induce the growth of lithium dendrites. In single-ion electrolytes, since negative ions are fixed and only lithium ions move, the effective conductivity is greatly improved and the growth of lithium dendrites is inhibited. Compared with liquid dual-ion electrolytes, since the movement speed of negative ions is much greater than that of lithium ions, and since only single ions (lithium ions) move in solid electrolytes, the ionic conductivity of single-ion electrolytes is often one to two orders of magnitude lower than that of conventional dual-ion electrolytes.
[0005] CN112952191A discloses the preparation and application of a high-performance single-ion polymer solid electrolyte, and specifically discloses a sulfonimide polymer single-ion solid electrolyte. However, the single-ion solid electrolyte uses a relatively expensive sulfonimide monomer, which is not conducive to further commercial production. Summary of the invention:
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a single-ion composite solid electrolyte. The single-ion composite solid electrolyte obtained by the preparation method has high ionic conductivity and lithium ion migration number, and is suitable for processing into a high-performance lithium-ion battery electrolyte membrane.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] The first object of the present invention is to provide a method for preparing a single ion composite solid electrolyte, the preparation method comprising the following steps:
[0009] S1, subjecting monomer vinyl ethylene carbonate and the compound represented by formula (I) to a polymerization reaction under the action of an initiator to obtain a polymerization product;
[0010] S2, dissolving the polymer product obtained in step S1, the polymer matrix and the lithium salt into an organic solvent to obtain a composite solid electrolyte solution;
[0011] S3, adding a lithium source to the composite solid electrolyte solution obtained in step S2 for lithiation treatment, removing the organic solvent, and obtaining a single-ion composite solid electrolyte;
[0012]
[0013] Among them, R 1 is selected from one of hydrogen, alkyl and alkenyl; R 2 It is an alkyl group.
[0014] The second object of the present invention is to provide a single ion composite solid electrolyte obtained by the aforementioned preparation method.
[0015] The third object of the present invention is to provide application of the aforementioned single ion composite solid electrolyte in lithium ion batteries.
[0016] A fourth object of the present invention is to provide a lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte is the aforementioned single ion composite solid electrolyte.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present invention utilizes the characteristics of vinyl ethylene carbonate that it is electron-attracting and has large steric hindrance, and introduces a sulfonic acid containing an amide group (the compound shown in Formula I) in view of its difficult homopolymerization. This substance can not only serve as a bridge for the polymerization reaction of vinyl ethylene carbonate to prepare a solid polymer electrolyte with a large molecular weight, but also can provide a sulfonic acid group for subsequent lithiation treatment.
[0019] 2. Ethylene carbonate is added to the polymer as a monomer for lithium ion transmission. Its unique cyclic ether and ketone structure can effectively dissolve lithium salts and directionally transmit lithium ions, thereby making the polymer have higher ionic conductivity.
[0020] 3. Compared with the sulfonic acid containing an amide group being first lithiated and then polymerized with vinyl ethylene carbonate, the ionic conductivity of the solid electrolyte prepared by the present invention by first polymerizing and then lithiating is nearly three times higher;
[0021] 4. Compared with sulfonic acid imide monomers, the raw materials in the present invention are widely available and cheap, and are suitable for industrial applications. Description of the drawings:
[0022] Figure 1 SEM images of pure PVDF (left) and the single-ion composite solid electrolyte prepared in Example 1 (right);
[0023] Figure 2 XRD pattern of the single ion composite solid electrolyte prepared in Example 1;
[0024] Figure 3 A schematic diagram of assembling a battery using the single-ion composite solid electrolyte prepared in Example 1;
[0025] Figure 4 is the infrared spectrum of the polymer product prepared in Example 1;
[0026] Figure 5 The EIS graph (upper figure) and chronoamperometry curve (lower figure) of a lithium / SPE / lithium symmetric battery assembled using the single ion composite solid electrolyte prepared in Example 1;
[0027] Figure 6 This is an EIS graph of a stainless steel / SPE / stainless steel symmetric cell assembled using the single ion composite solid electrolyte prepared in Example 1;
[0028] Figure 7 The LSV diagram of the stainless steel / SPE / Li half-cell assembled using the single-ion composite solid electrolyte prepared in Example 1;
[0029] Figure 8 The AC impedance spectra of the stainless steel / SPE / stainless steel symmetrical cells assembled using the single ion composite solid electrolytes prepared in Example 1 and Comparative Examples 6 to 8 are shown. Specific implementation method:
[0030] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0031] The present invention provides a method for preparing a single-ion composite solid electrolyte, the preparation method comprising the following steps:
[0032] S1, subjecting monomer vinyl ethylene carbonate and the compound represented by formula (I) to a polymerization reaction under the action of an initiator to obtain a polymerization product;
[0033] S2, dissolving the polymer product obtained in step S1, the polymer matrix and the lithium salt into an organic solvent to obtain a composite solid electrolyte solution;
[0034] S3, adding a lithium source to the composite solid electrolyte solution obtained in step S2 for lithiation treatment, removing the organic solvent, and obtaining a single-ion composite solid electrolyte;
[0035]
[0036] Among them, R 1 is selected from one of hydrogen, alkyl and alkenyl; R 2 It is an alkyl group.
[0037] In the present invention, in formula (I), R 1 It is selected from one of hydrogen, C1-C12 alkyl, C1-C12 alkenyl; preferably one of hydrogen, C1-C6 alkyl and C1-C6 alkenyl; for example, it can be one of hydrogen, vinyl, propenyl, methyl, ethyl, n-propyl and isopropyl.
[0038] Preferably, R 2 The C1-C12 alkyl group may be a straight-chain alkyl group or an alkyl group having a branched structure; further, it is preferably a C1-C6 alkyl group; more preferably, it is one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.
[0039] Exemplarily, the compound shown in formula (I) is Hereinafter referred to as AMPS.
[0040] In a further technical solution, the mass ratio of the vinyl ethylene carbonate to the sulfonic acid containing an amide group (the compound represented by formula (I)) is (2.5-10):1.
[0041] In a further technical solution, the reaction temperature of the polymerization reaction is 45-90°C, and the reaction time is 8-16h. If the reaction time is too short, the polymerization reaction is not sufficient, and the product obtained by polymerization is liquid or liquid, that is, a solid electrolyte cannot be obtained; if the reaction time is too long, the degree of polymerization of the product will be deepened, the movement of molecules will become more difficult, and the ability to transport lithium ions will continue to decrease, resulting in a decrease in ionic conductivity. In addition, the rate at which polymer electrolytes transport lithium ions is slower than the rate at which they transport anions. As the molecular weight of the polymer increases, the gap between the transport capacity of lithium ions and the transport capacity of anions further increases, so that the lithium ion migration number gradually decreases.
[0042] In a further technical solution, since vinyl ethylene carbonate is an electron-withdrawing monomer and has large steric hindrance, polymerization is relatively difficult. A solid-state polymerization product with a higher molecular weight can be prepared by adding an initiator. Under preferred conditions, the initiator is selected from one or more oil-soluble initiators such as azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
[0043] In a further technical solution, the amount of the initiator is more than 1% of the total weight of the monomer. When the amount of the initiator is too low, the obtained polymerization product is a mixture of polymers and oligomers. Due to the low molecular weight of the oligomers, their ionic conductivity is high; when the amount of the initiator is higher than 1%, as the amount of the initiator increases, the ionic conductivity and impedance of the product gradually increase. This is because the increase in the amount of the initiator leads to a continuous deepening of the polymerization degree of the polymer, the movement of the molecules becomes more and more difficult, and the ability to transport lithium ions is continuously reduced, so that the ionic conductivity gradually decreases and the impedance gradually increases.
[0044] The solid electrolyte obtained by direct lithiation of the polymer product obtained in step S1 of the present invention is very brittle and is easily crushed during battery assembly, thereby causing a short circuit of the positive and negative electrodes. A soft solid electrolyte separator can be formed by adding a polymer matrix having a skeleton effect, thereby facilitating battery assembly. Under preferred conditions, the polymer matrix is selected from one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polymethyl methacrylate (PMMA), but is not limited thereto.
[0045] In a further technical solution, in step S2, the lithium salt is selected from LiClO 4 、LiPF 6 , LiBF 4 、LiAsF 4, LiTFSI, LiFSI or more thereof, but not limited thereto. The lithium salt is used as a cosolvent for poly(ethylene carbonate)(2-acrylamide-2-methylpropanesulfonic acid), and its dissolution temperature in an organic solvent is 60 to 80°C.
[0046] In a further technical solution, in step S2, the mass ratio of the polymerization product obtained in step S1 to the polymer matrix and the lithium salt is (1-5):(1-5):1.
[0047] The present application has no special requirements for the type of the organic solvent, as long as it can dissolve the polymerization product, polymer matrix and lithium salt obtained in step S1. Exemplarily, the organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, and acetonitrile, but is not limited thereto.
[0048] In a further technical solution, the lithium source is lithium hydroxide; and the molar ratio of the lithium source to the compound represented by formula (I) is 1:1.
[0049] The present invention provides a single ion composite solid electrolyte obtained by the above-mentioned preparation method.
[0050] The present invention also provides application of the above-mentioned single ion composite solid electrolyte in lithium ion batteries.
[0051] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte, wherein the solid electrolyte is the above-mentioned single ion composite solid electrolyte.
[0052] In the present invention, the types of the positive electrode and the negative electrode of the lithium-ion battery are well known to those skilled in the art, and will not be described in detail in this application.
[0053] The performance tests of the solid electrolytes prepared in the following examples and comparative examples are as follows:
[0054] Figure 3 Schematic diagram of assembling a battery with a single-ion composite solid electrolyte. Different types of batteries can be obtained by changing the types of positive and negative electrodes according to actual needs.
[0055] Lithium battery assembly:
[0056] In a glove box, the solid electrolyte and two stainless steel sheets were assembled into a stainless steel / SPE / stainless steel symmetrical cell. The cell was subjected to electrochemical impedance spectroscopy at 25 °C to obtain the bulk impedance of the SPE, which was then substituted into formula (1) to calculate the ionic conductivity of the solid electrolyte.
[0057] σ=L / RS Formula (1)
[0058] Wherein, σ is the ionic conductivity, L is the thickness of the solid electrolyte, R is the bulk impedance, and S is the area of the solid electrolyte.
[0059] In a glove box, the solid electrolyte was assembled with two lithium metal sheets into a lithium / SPE / lithium symmetrical battery. The battery was subjected to a comprehensive test of DC polarization and AC impedance at 25°C and was substituted into formula (2) to determine the lithium ion migration number of the solid electrolyte.
[0060]
[0061] Among them, t Li+ is the lithium ion migration number, I ss is the steady-state current, I 0 is the initial current, ΔV is the polarization voltage, R ss is the steady-state interface impedance, R 0 is the initial interface impedance.
[0062] In the glove box, a stainless steel / SPE / Li half-cell was assembled with a lithium metal sheet as the negative electrode, a stainless steel gasket as the positive electrode, and an SPE inserted therein. The battery was subjected to a linear sweep voltammetry test at 25°C. The battery was tested at 0.5 mVs -1 The electrochemical window of the solid electrolyte was tested in the scan rate range of 2 to 6 V.
[0063] In the following examples, VEC is vinyl ethylene carbonate, AMPS is 2-acrylamide-2-methylpropanesulfonic acid, PVDF is polyvinylidene fluoride, and AIBN is azobisisobutyronitrile.
[0064] Example 1
[0065] S1. Add monomers VEC and AMPS into dimethyl sulfoxide at a mass ratio of 5:1, and then add 1% AIBN of the total weight of the monomers, react at 70°C for 8h, and place in a vacuum drying oven at 80°C after the reaction to volatilize excess organic reagents to obtain a polymerization product.
[0066] S2, the above-mentioned polymerization product, PVDF, LiClO 4 The mixture was dissolved in N,N-dimethylformamide in a mass ratio of 3:3:2, heated to 70° C. and stirred to dissolve, thereby obtaining a composite solid electrolyte solution.
[0067] S3. Add lithium hydroxide in a molar ratio of 1:1 to 2-acrylamide-2-methylpropanesulfonic acid to the above-mentioned composite solid electrolyte solution, stir at room temperature for 6 hours for lithiation treatment, remove the air therein by ultrasound, pour into a polytetrafluoroethylene plate, place in a vacuum drying oven at 80°C, evaporate excess organic solvent, and obtain a single-ion composite solid electrolyte (SPE).
[0068] Figure 1 The SEM images of pure PVDF (left) and the single ion composite solid electrolyte prepared in Example 1 (right). Figure 1 It can be seen that pure PVDF is a porous structure, and the polymerization product can be well filled into the pores of PVDF to form a complete ion channel, thereby realizing a coherent ion conduction pathway.
[0069] Figure 2 The XRD pattern of the single ion composite solid electrolyte (SPE) prepared in Example 1 is as follows: Figure 2 There is no sharp characteristic peak of lithium salt in the XRD pattern of the product, indicating that the single-ion composite solid electrolyte prepared in Example 1 has good solubility for lithium salt.
[0070] Figure 4 The infrared spectrum of the polymer product prepared in Example 1. Figure 4 It can be seen that the infrared spectrum contains infrared functional groups of both vinyl ethylene carbonate and lithium 2-acrylamide-2-methylpropanesulfonate, which proves the successful preparation of the polymerization product.
[0071] Figure 5 The EIS graph and chronoamperometry curve of the lithium / SPE / lithium symmetric battery assembled with the single-ion composite solid electrolyte membrane prepared in Example 1 show that the lithium ion migration number is 0.676, which is much higher than 0.2-0.4 of the dual-ion electrolyte, proving the successful preparation of the single-ion electrolyte.
[0072] Figure 6 This is an EIS graph of a stainless steel / SPE / stainless steel symmetric battery assembled using the single-ion composite solid electrolyte membrane prepared in Example 1. The bulk impedance is 216Ω at 25°C.
[0073] Figure 7 The LSV diagram of the stainless steel / SPE / Li half-cell assembled with the single-ion composite solid electrolyte prepared in Example 1 shows that the electrochemical window is 4V and the cell can withstand a voltage of 5V for a considerable period of time.
[0074] Examples 2 to 4 and Comparative Example 1
[0075] The method of Example 1 is followed, except that the polymerization reaction time in step S1 is changed, as shown in Table 1.
[0076] The morphologies of the polymer products prepared in Examples 1 to 4 and Comparative Example 1 are shown in Table 1.
[0077] The test results of ion conductivity, ion migration number, lithium ion migration number and impedance of the battery assembled with the single ion composite solid electrolyte prepared in Examples 1 to 4 and Comparative Example 1 are shown in Table 1.
[0078] Table 1
[0079]
[0080] From Table 1 we can see that:
[0081] When the reaction time is 4h, due to incomplete polymerization and low molecular weight, the prepared polymer product is liquid and does not meet the category of polymer solid electrolyte. When the reaction time is 8-20h, the prepared polymer product is solid and meets the category of polymer solid electrolyte.
[0082] As the reaction time increases, the ionic conductivity shows a trend of gradually decreasing. This is mainly because as the reaction time increases, the degree of polymerization continues to deepen, the movement of molecules becomes more difficult, and the ability to transport lithium ions continues to decrease, so the ionic conductivity gradually decreases. The rate at which polymer electrolytes transport lithium ions is slower than the rate at which they transport anions. As the molecular weight of the polymer increases, the gap between the transport capacity of lithium ions and the transport capacity of anions further increases, so the lithium ion migration number gradually decreases.
[0083] For polymers, electrical conductivity is divided into ionic conductivity and electronic conductivity. A good polymer solid electrolyte requires the ionic conductivity to be as high as possible, and the electronic conductivity to be as low as possible. The ion migration number shows the proportion of ionic conductivity, which is generally required to be above 0.9. The ion migration number of the solid electrolyte prepared in Examples 1 to 4 is 0.98 to 0.99, indicating that it has good ionic conductivity and meets the requirements of solid electrolytes for lithium-ion batteries. However, the impedance of the solid electrolyte prepared in Comparative Example 1 is too high, which affects the transmission of lithium ions, so the reaction time needs to be controlled at 8 to 16 hours.
[0084] Examples 5-6 and Comparative Examples 2-3
[0085] The method of Example 1 was followed, except that the amount of the initiator in step S1 was changed, as shown in Table 2.
[0086] The morphologies of the polymer products prepared in Examples 5-6 and Comparative Examples 2-3 are shown in Table 2.
[0087] The test results of ion conductivity, ion migration number, lithium ion migration number and impedance of the battery assembled using the single ion composite solid electrolyte prepared in Examples 5 to 6 and Comparative Examples 2 to 3 are shown in Table 2.
[0088] Table 2
[0089]
[0090] From Table 2 we can see that:
[0091] When the amount of initiator is less than 1%, the polymerization product is in liquid form. This may be because when the initiator content is low, the product obtained is in the form of coexistence of polymer and oligomer. Due to the low molecular weight of the oligomer, its ionic conductivity is higher.
[0092] When the amount of initiator is higher than 1%, the ionic conductivity and impedance of the product gradually increase with the increase of the amount of initiator. This is because the increase in the amount of initiator leads to a continuous deepening of the polymerization degree of the polymer, the movement of molecules becomes more difficult, and the ability to transport lithium ions continues to decrease, so that the ionic conductivity gradually decreases and the impedance gradually increases.
[0093] Examples 7-8 and Comparative Examples 4-5
[0094] The method of Example 1 is followed, except that the mass ratio of VEC to AMPS in step S1 is changed, as shown in Table 3.
[0095] The test results of ion conductivity, ion migration number, lithium ion migration number and impedance of the battery assembled using the single ion composite solid electrolyte prepared in Examples 7 to 8 and Comparative Examples 4 to 5 are shown in Table 3.
[0096] Table 3
[0097]
[0098] From Table 3 we can see that:
[0099] As the mass ratio of VEC and AMPS decreases, the impedance shows a trend of first decreasing and then increasing, and the ionic conductivity shows a trend of first increasing and then decreasing. This is mainly because AMPS has amide and sulfonic acid groups, which can promote the increase of ionic conductivity and reduce impedance. However, lithium 2-acrylamide-2-methylpropane sulfonate itself has no ionic conductivity. Therefore, when the content of lithium 2-acrylamide-2-methylpropane sulfonate reaches a certain value, it will prevent ion transmission, thereby reducing ionic conductivity and increasing impedance.
[0100] The lithium ion migration number gradually increases with the increase of AMPS dosage. This is because AMPS and lithium hydroxide react to form a single ion source. Therefore, the higher the content of lithium 2-acrylamide-2-methylpropane sulfonate, the more single ion sources there are, and the higher the lithium ion migration number.
[0101] Therefore, it is more appropriate to control the mass ratio of VEC to AMPS at (5-10):1.
[0102] Comparative Example 6
[0103] In this comparative example, AMPS is firstly subjected to lithiation treatment and then polymerized with VEC.
[0104] S1. Add AMPS and lithium hydroxide into dimethyl sulfoxide in a molar ratio of 1:1, and stir for 6 hours for lithiation treatment.
[0105] S2. Add VEC to the solution obtained in step S1 at a mass ratio of VEC to AMPS of 5:1, and then add 1% AIBN of the total weight of the monomers, react at 70°C for 8h, and after the reaction, place in a vacuum drying oven at 80°C to volatilize excess organic reagents to obtain a polymerization product.
[0106] S3, the polymer product obtained in step S2, PVDF, LiClO 4 The solid electrolyte solution was dissolved in N,N-dimethylformamide at a mass ratio of 3:3:2, heated to 70°C and stirred to obtain a composite solid electrolyte solution; the air was then removed by ultrasound, poured into a polytetrafluoroethylene plate, and placed in a vacuum drying oven at 80°C to evaporate excess organic solvent to obtain a single-ion composite solid electrolyte.
[0107] Comparative Example 7
[0108] According to the method of Example 1, except that vinylene carbonate is used instead of vinyl ethylene carbonate, the specific steps are as follows:
[0109] S1. Add vinylene carbonate and AMPS monomers into dimethyl sulfoxide in a mass ratio of 5:1, and then add 1% of the total mass of AIBN into the monomers, react at 70°C for 8h, and place in a vacuum drying oven at 80°C after the reaction to volatilize excess organic reagents to obtain a polymerization product.
[0110] S2, the polymer product obtained in step S1, PVDF, LiClO 4 The mixture was dissolved in N,N-dimethylformamide in a mass ratio of 3:3:2, heated to 70° C. and stirred to dissolve, thereby obtaining a composite solid electrolyte solution.
[0111] S3. Add lithium hydroxide in a molar ratio of 1:1 to 2-acrylamide-2-methylpropanesulfonic acid to the composite solid electrolyte solution obtained in step S2, stir at room temperature for 6 hours for lithiation treatment, remove air therefrom by ultrasound, pour into a polytetrafluoroethylene plate, place in a vacuum drying oven at 80° C., volatilize excess organic solvent, and obtain a single-ion composite solid electrolyte.
[0112] Comparative Example 8
[0113] The method of Example 1 is followed, except that the polyethylene carbonate and the lithium poly-2-acrylamide-2-methylpropanesulfonate are physically mixed, and the specific steps are as follows:
[0114] S1. Stir the monomer VEC and 1% by weight of AIBN until dissolved, react at 70° C. for 8 h, and dry in a vacuum drying oven at 80° C. after the reaction to obtain polyvinyl ethylene carbonate.
[0115] S2. The monomer AMPS and 1% AIBN by mass are dissolved in dimethyl sulfoxide, reacted at 70°C for 8 hours, and then lithium hydroxide is added in a molar ratio of 1:1 with 2-acrylamide-2-methylpropane sulfonic acid, stirred at room temperature for 6 hours for lithiation treatment, and dried in a vacuum drying oven at 80°C to obtain poly 2-acrylamide-2-methylpropane sulfonate lithium.
[0116] S3, the polyethylene carbonate obtained in step S1, the poly (2-acrylamide-2-methylpropanesulfonic acid lithium) obtained in step S2, PVDF, LiClO 4 The solid electrolyte solution was dissolved in N,N-dimethylformamide in a mass ratio of 2.5:0.5:3:2, heated to 70°C and stirred to dissolve, thereby obtaining a composite solid electrolyte solution; the air therein was then removed by ultrasound, poured into a polytetrafluoroethylene plate, and placed in a vacuum drying oven at 80°C to volatilize excess organic solvent, thereby obtaining a single-ion composite solid electrolyte.
[0117] The test results of ion conductivity, ion migration number, lithium ion migration number and impedance of the battery assembled using the single ion composite solid electrolyte prepared in Comparative Examples 6 to 8 are shown in Table 4.
[0118] Table 4
[0119]
[0120] From Table 4 we can see that:
[0121] Compared with Example 1, in Comparative Example 6, VEC and AMPS were first subjected to lithiation treatment and then to polymerization reaction, and the ionic conductivity and impedance of the obtained product were significantly reduced.
[0122] The ionic conductivity and impedance of Comparative Example 7 are significantly worse than those of Example 1, indicating that the solid electrolyte obtained by using vinylene carbonate instead of vinyl ethylene carbonate does not meet the use requirements.
[0123] The product obtained in Comparative Example 8 is in liquid state, so its ionic conductivity and impedance are comparable to those of Example 1, but it cannot be used as a solid electrolyte.
[0124] In summary, only by first polymerizing VEC and AMPS to form a polymer product and then lithiating it can a solid electrolyte with high ionic conductivity and lithium ion transfer number be prepared.
[0125] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a single-ion composite solid electrolyte, characterized in that: The preparation method comprises the following steps: S1, subjecting monomer vinyl ethylene carbonate and the compound represented by formula (I) to a polymerization reaction under the action of an initiator to obtain a polymerization product; S2, dissolving the polymer product obtained in step S1, the polymer matrix and the lithium salt into an organic solvent to obtain a composite solid electrolyte solution; S3, adding a lithium source to the composite solid electrolyte solution obtained in step S2 for lithiation treatment, removing the organic solvent, and obtaining a single-ion composite solid electrolyte; Wherein, R1 is selected from one of hydrogen, alkyl, and alkenyl; R2 is alkyl; The reaction temperature of the polymerization reaction is 45-90° C., and the reaction time is 8-16 hours.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the vinyl ethylene carbonate to the compound represented by formula (I) is (2.5-10):
1.
3. The preparation method according to claim 1, characterized in that: The initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile or benzoyl peroxide.
4. The preparation method according to claim 1, characterized in that: The amount of the initiator used is more than 1% of the total weight of the monomers.
5. The preparation method according to claim 1, characterized in that: The polymer matrix is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber, carboxymethyl cellulose, polyvinyl alcohol, and polymethyl methacrylate.
6. The preparation method according to claim 1, characterized in that: The lithium salt is selected from one or more of LiClO4, LiPF6, LiBF4, LiAsF4, LiTFSI, and LiFSI.
7. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the polymerization product to the polymer matrix and the lithium salt is (1-5):(1-5):
1.
8. The preparation method according to claim 1, characterized in that: The organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and acetonitrile.
9. The preparation method according to claim 1, characterized in that: The molar ratio of the lithium source to the compound represented by formula (I) is 1:
1.
10. The preparation method according to claim 1, characterized in that: R1 is selected from one of hydrogen, C1-C12 alkyl, and C1-C12 alkenyl.
11. The preparation method according to claim 10, characterized in that: R1 is one of hydrogen, C1-C6 alkyl, and C1-C6 alkenyl.
12. The preparation method according to claim 1, characterized in that: R2 is a C1-C12 alkyl group.
13. The preparation method according to claim 12, characterized in that: R2 is a C1-C6 alkyl group.
14. The preparation method according to claim 13, characterized in that: R2 is one of ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.
15. A single ion composite solid electrolyte obtained by the preparation method according to any one of claims 1 to 14.
16. Use of the single-ion composite solid electrolyte according to claim 15 in lithium-ion batteries.
17. A lithium ion battery comprising a positive electrode, a negative electrode and a solid electrolyte, characterized in that: The solid electrolyte is the single ion complex solid electrolyte according to claim 15.
Citation Information
Patent Citations
Method for semi-interpenetrating network-structure similar-single ion solid-state polymer electrolyte by in-situ polymerization method
CN107919496A
Preparation method and application of high-performance single-ion polymer solid electrolyte
CN112952191A